Co-Educar y Co-Enseñar derechos humanos: algunas propuestas - Sánchez Rubio, David (Universidade de Brasília, 2017)
This article will focus on the importance of a figure or concept, such as human rights, which can serve as a mechanism with which human beings can access in a more just, equitable and proportionate way, material goods and immaterial with which to live worthily in every society that is said to be democratic, constitutional and law. For that reason we will try to refine by stopping with some proposals and guidelines of what can be an education that sensitize us for and in human rights. Without a culture that wants and bets on them, it will be difficult for the political and legal rules of play agreed by consensus to work in a distributive and fair way, and it would also be difficult to make the set of responsibilities, rights and obligations, principles and values that we must know, assume, fulfill, act and develop to live with a practice with dignity, equity, freedom, equality, peace, solidarity, plurality of differences and democracy